Ethyl acetate fractions of Cordyline fruticosa leaf: Chemical composition and cariogenic antimicrobial activity - Alphianti, Likky Tiara; Bachtiar, Endang Winiati; Suniarti, Dewi Fatma; Fauziah, Eva (Universitas Padjadjaran, 2025)
Introduction: Early childhood caries (ECC) is a prominent oral health problem, especially among low socioeconomic status (SES) groups. The development of herbal agents for caries prevention is essential due to the elevated costs and potential adverse effects linked to existing synthetic pharmaceuticals. Cordyline fruticosa (L.) A. Chev. (CF), prevalent in Indonesian rural regions, is an ornamental plant recognised for its medicinal properties, especially its antimicrobial efficacy. This study aimed to identify the chemical compounds in the ethyl acetate fraction of CF leaf extract and evaluate its antibacterial and antifungal activities against Streptococcus mutans (S. mutans) and Candida albicans (C. albicans), the main microorganisms associated with early childhood caries. Methods: This study used a laboratory experimental method. CF leaf extract was fractionated using ethyl acetate. Phytochemical and GC-MS screening were performed to identify secondary metabolites and chemical compounds. S. mutans and C. albicans were isolated from supragingival plaque samples of pediatric patients with severe ECC. The Minimum Inhibitory Concentration (MIC) was determined via serial dilution and ELISA spectrophotometry by comparing absorbance or optical density (OD) values before and after incubation.Results: Phytochemical screening confirmed the presence of phenolic compounds, flavonoids, tannins, and triterpenoids. GC-MS identified 4 chemical compounds, of which the largest peak area (73.88%) corresponding to 5-hydroxymethylfurfural. The MIC for S. mutans was 3.125% and 1.56% for C. albicans. Conclusion: The ethyl acetate fraction of the CF leaf extract exhibits antibacterial and antifungal properties and may function as a cariogenic antimicrobial agent.